Different Characteristics of Aquaporin-4 and Myelin Oligodendrocyte Glycoprotein Antibody-Seropositive Male Optic Neuritis in China. (1st April 2019) - Song, Honglu; Zhou, Huanfen; Yang, Mo; Wang, Junqing; Liu, Hongjuan; Sun, Mingming; Xu, Quangang; Wei, Shihui
Abstract : Purpose . To describe different clinical characteristics and prognosis of optic neuritis (ON) in male patients with seropositive aquaporin-4 antibody (AQP4-Ab) or myelin oligodendrocyte glycoprotein antibody (MOG-Ab) in China. Method . Males with ON were recruited from the Neuro-ophthalmology Department of the Chinese People's Liberation Army, General Hospital from January 2016 to February 2018. They were assigned to two groups based on antibodies status: MOG-Ab-seropositive ON (MOG-ON) and aquaporin-4 Ab-seropositive ON (AQP4-ON). Results . Seventy-six male patients were assessed, including 44 MOG-ON (57.9%) and 32 AQP4-ON (42.1%). The MOG-ON patients were significantly younger at onset compared to the AQP4-ON group (p < 0.001 ). Frequencies of optic disc swelling, presence of abnormal autoimmune antibodies, and elevated levels of CSF IgG were significantly higher in the AQP4-ON group than the MOG-ON group (p = 0.040, p = 0.016, andp = 0.10, respectively). At the final visit, 85.3% of MOG-ON eyes had increased visual acuity (≥0.5) compared to 35.1% of AQP4-ON eyes (p < 0.001 ). The ratio of this steroid-dependent condition is higher in MOG-ON patients than the AQP4-ON group (p < 0.001 ). The ratio of conversion to NMO is higher in the AQP4-ON group than the MOG-ON group, with more AQP4-ON patients developing NMO by the follow-up (p = 0.012 ). MOG-ON patients had thicker average peripapillary retinal nerve fiber layers and macular ganglion cell-inner plexiform than AQP4-ON patients (p = 0.008 andp = 0.012, respectively). Orbital MRI revealed more AQP4-ON patients had chiasmal involvement than MOG-ON patients (p < 0.001 ). Conclusion . Male MOG-ON patients had different clinical features including earlier age of onset, higher optic disc swelling ratio, better visual acuity recovery, thicker peripapillary retinal nerve fiber and macular ganglion cell-inner plexiform layers, and less chiasmal involvement than male AQP4-ON patients. Serum antibody may be a potential biomarker for determining visual prognosis in male ON.